2016
DOI: 10.1590/0001-3765201620160386
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the knowledge of the chemical structure of glycoconjugates from Trypanosoma cruzi TcI genotype. Contribution to taxonomic studies

Abstract: One of the main obstacles to the treatment of Chagas disease is the genetic and phenotypical variance displayed by T. cruzi strains, resulting in differences in morphology, virulence, pathogenicity and drug susceptibility. To better understand the role of glycoconjungates in Chagas disease, we performed the molecular characterization of the O-linked chains from mucins and glycoinositolphospholipids (GIPLs) of the Silvio X10 clone 1 strain. We demonstrated the presence of a β-galactofuranose (β-Galf) unity link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…On studying the fine structure of the glycans in several strains, it was concluded that core 2 was found in the mucins of strains belonging to DTU I isolated from sylvatic hosts, namely G strain [ 47 , 48 ], Colombiana [ 50 ], Dm28c [ 49 ] and Silvio X10/1 [ 85 ], and also in the hybrid Tulahuen strain [ 51 ], classified as DTU VI. A sialylated oligosaccharide was also identified in the mucins from Dm28c.…”
Section: Structure Of O -Glycans In Mucins Of Ementioning
confidence: 99%
“…On studying the fine structure of the glycans in several strains, it was concluded that core 2 was found in the mucins of strains belonging to DTU I isolated from sylvatic hosts, namely G strain [ 47 , 48 ], Colombiana [ 50 ], Dm28c [ 49 ] and Silvio X10/1 [ 85 ], and also in the hybrid Tulahuen strain [ 51 ], classified as DTU VI. A sialylated oligosaccharide was also identified in the mucins from Dm28c.…”
Section: Structure Of O -Glycans In Mucins Of Ementioning
confidence: 99%